Spatiotemporal initiation and assembly dynamics of polar flagellation in γ-proteobacteria - Hook, John Christopher; Justus Liebig University Giessen (My University, 2022)
Bacterial motility, more precisely bacterial flagellation, is an extremely complex topic due to the plethora of mechanisms and factors involved in the precise assembly and functioning of flagellar structures. This high complexity in part originates in various flagellation patterns employed by different bacterial species, with some possessing randomly positioned flagellar structures, while others position their flagella in a targeted fashion at the cell pole. A factor, which is essential for this spatially constricted positioning of flagellar structures occurring in many bacterial species, is the SRP-GTPase FlhF. This factor has, in a multitude of publications, been established as the prime element in determining the construction site of the flagellum, as it arrives at the site of flagellar assembly prior to other structural components of the flagellum and the loss of FlhF leads to a randomly positioned flagellar structure. While the positioning of the flagellum has always been attributed to FlhF, the targeting mechanism, utilised by FlhF, to reach the cell pole, has not been determined. This study aimed to shed a light on this insufficiently analysed stage in the establishment process of flagella meditated motility. In line with this goal a novel factor named FipA, which governs the polar targeting behaviour of FlhF through direct interaction in a partially co-dependent manner, was discovered in Shewanella putrefaciens CN-32 and Pseudomonas putida KT2440. Here FipA is presumed to anchor FlhF at the cell pole through its predicted N-terminal transmembrane domain, while the C-terminal domain of FipA, comprising a DUF2802 domain, appears to interact with the N-terminal B-domain of FlhF. Due to the variability of the FlhF B-domain in different bacterial species and the observed differences in FipA functioning between the monotrichously flagellated Shewanella putrefaciens CN-32 and lophotrichously flagellated Pseudomonas putida KT2440, this interaction is postulated to account for variations in flagellation occurring in different bacterial species. Additionally, the ability of FipA to interact C-terminally with the C-terminal region of FlhF and the absence of interaction in the context of a FlhF variants, which are incapable of homodimerizing with their C-terminal G-domain, implies FipA requiring FlhF homodimerization prior to FlhF/FipA interaction. Here the ability to interact in this terminus configuration, while FipA also is able to interact with the N-terminal region of FlhG, which contains the activator helix, required for the induction of the FlhF GTPase activity, points towards an additional involvement of FipA in not just the polar recruitment of FlhF but also the disbanding of the FlhF homodimer. Besides elucidating the mechanisms and factors involved in the initiation phase of flagellar assembly, this study focused on characterising a unique C-terminal motif in the flagellar type 3 secretion system component FlhB in Shewanella putrefaciens CN-32 1. In the flagellar assembly process FlhB is essential for the export of extracellular flagellum components and, besides, together with FliK, being involved in the determination of the hook length, enables an export switching from hook associated proteins to filament associated proteins upon hook completion. This switch in export specificity occurs due to autocleavage of the cytoplasmic domain of FlhB, designated as FlhB-C, into the two distinct subdomains FlhB-CN and FlhB-CC. The peculiar motif characterised in this study is positioned in FlhB-CC and distinguishes itself through a high proline density, which is why it was appropriately named “Proline Rich Region” or in short PRR. Through the gathered data it was possible to determine the FlhB PRR an element, which influences hook assembly, the ability of FlhB-C to perform autocleavage and, by enabling an efficient export of filament subunits, the process of filament assembly. While phases downstream from the construction of the basal section of the flagellum, appear affected by the loss of the PRR, the general stability and formation of the C-ring indicated by FliM, unlike in the case of complete flhB deletion, is not affected. With the PRR motif being conserved in the FlhB of many β- and γ-proteobacteria, it presents itself as a factor, which enables the efficient assembly of extracellular substructures of the flagellum, while at the same time supporting the ability of FlhB to autocleave.
Keywords: Molekularbiologie; Mikrobiologie; ddc:500